Advancements in microalgal biomass conversion for rubber composite applications - Doaa S. Mahmoud; Salwa H. El-Sabbagh; Sayeda M. Abdo (Scientific Reports)
Abstract Carbon black (CB) as rubber reinforcement has raised environmental concerns regarding this traditional petroleum-based filler, which is less susceptible to biodegradability. Although it has great reinforcing properties, the production technique is no longer sustainable, and its cost increases regularly. For these reasons, it is wise to look for sustainable replacement materials. Microalgal biomass (MB) has demonstrated great potential for use as biodegradable nano fillers in rubber composites. Microalgal has a high biomass productivity compared to traditional crops. They can produce a large amount of biomass per unit of land area, making them highly efficient in terms of resource utilization. In the present research, microalgal biomass was blended with CB at different concentrations for preparing two different kinds of rubber composites: Nitrile rubber Acrylonitrile-butadiene rubber (NBR) and styrene-butadiene rubber (SBR) are two common synthetic rubbers. In this study, the researchers investigated using microalgal biomass as filler in rubber composites. They assessed the filler-matrix interaction by evaluating the processability, mechanical characteristics, Payne effect, and swelling properties of the MB/CB-filled composites and compared them to CB-filled composites. The results show that rubber composites incorporating dual fillers (microalgal biomass and carbon black) had faster cure times, increased torque, and improved mechanical properties. The results prove biomass helps to minimize bulk quantities of CB and may be used as a partial replacement while still improving the mechanical properties. According to the study, microalgal biomass can successfully replace up to 50% of the CB filler. This will reduce petroleum dependence and possibly costs, depending on current petroleum prices.